2018
DOI: 10.1002/jia2.25118
|View full text |Cite
|
Sign up to set email alerts
|

What would you choose: Online or Offline or Mixed services? Feasibility of online HIV counselling and testing among Thai men who have sex with men and transgender women and factors associated with service uptake

Abstract: Introduction HIV testing coverage remains low among men who have sex with men (MSM) and transgender women (TGW). We studied characteristics of Thai MSM and TGW who chose online and/or offline platforms for HIV counselling and testing and the feasibility of integrating online technologies and HIV self‐testing to create service options.MethodsFrom December 2015 to June 2017, MSM and TGW enrolled from Bangkok Metropolitan Region and Pattaya could choose between: 1 offline HIV counselling and testing (Offline grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 19 publications
2
61
0
Order By: Relevance
“…The study was supported by amfAR GMT Initiative grant. Factors associated with preferences for online or offline HIV services at study entry were previously reported . Here we reported findings on seroconversion, retention and linkages to HIV confirmatory testing and ART initiation during the 12‐month study period.…”
Section: Methodsmentioning
confidence: 54%
See 3 more Smart Citations
“…The study was supported by amfAR GMT Initiative grant. Factors associated with preferences for online or offline HIV services at study entry were previously reported . Here we reported findings on seroconversion, retention and linkages to HIV confirmatory testing and ART initiation during the 12‐month study period.…”
Section: Methodsmentioning
confidence: 54%
“…We previously reported that the use of online, supervised, HIV self‐testing is feasible in Thailand and has potential to engage a high proportion of MSM and TGW who are first‐time testers and those with high HIV prevalence . In this paper, we demonstrated that MSM and TGW who chose to have online, supervised, HIV self‐testing had a high HIV incidence at 5.2 per 100 person‐years.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…A study from Thailand also demonstrates the promise of leveraging technology and self‐testing to improve reach and testing uptake among MSM and transgender women . In this study, Phanuphak et al .…”
Section: Innovations In Hiv Testing Modalities and Linkage To Treatmentmentioning
confidence: 73%